The Chinese pine genome and methylome unveil key features of conifer evolution - Niu, Shihui; Li, Jiang; Bo, Wenhao; Yang, Weifei; Zuccolo, Andrea; Giacomello, Stefania; Chen, Xi; Han, Fangxu; Yang, Junhe; Song, Yitong; Nie, Yumeng; Zhou, Biao; et al. (Cell, 2022)
Conifers dominate the world’s forest ecosystems and are the most widely planted tree species. Their giant and complex genomes present great challenges for assembling a complete reference genome for evolutionary and genomic studies. We present a 25.4-Gb chromosome-level assembly of Chinese pine (Pinus tabuliformis) and revealed that its genome size is mostly attributable to huge intergenic regions and long introns with high transposable element (TE) content. Large genes with long introns exhibited higher expressions levels. Despite a lack of recent whole-genome duplication, 91.2% of genes were duplicated through dispersed duplication, and expanded gene families are mainly related to stress responses, which may underpin conifers’ adaptation, particularly in cold and/or arid conditions. The reproductive regulation network is distinct compared with angiosperms. Slow removal of TEs with high-level methylation may have contributed to genomic expansion. This study provides insights into conifer evolution and resources for advancing research on conifer adaptation and development. [Display omitted] •Chromosome-level assembly and methylome of the largest gymnosperm genome so far•Continuous expansion and slow removal of transposons cause conifer huge genome•Large genes with ultra-long introns tend to be expressed at higher levels•Distinctive reproductive evolutionary trajectory compared to angiosperms Assembly of the Chinese Pine giga-genome reveals insights into conifer evolution and provides a resource for studies on conifer adaptation and development.